Effect of carbonization temperature on properties of aligned electrospun polyacrylonitrile carbon nanofibers. (15th November 2015) - Liu, Cheng-Kun; Feng, Yan; He, Hai-Jun; Zhang, Jing; Sun, Run-Jun; Chen, Mei-Yu
Abstract: Aligned electrospun nanofibrous bundle was used as the raw material for pretreatment, preoxidation and carbonization processes to prepare carbon nanofibers in a procedure temperature-controlled sintering furnace. Effect of carbonization temperature on the morphology and structural performance of nanofibers was investigated in present study. Results showed that R I (the relative intensity radio between Disordered peak and Graphite peak) of nanofibers carbonized at 1000 °C is 0.90, carbon content is up to 85.67%, conductivity is 105.44 S·cm − 1, Young's modulus is 68.8 ± 0.42 GPa, and fiber strength is 306.0 ± 9.0 MPa, all of which endow the fibers with a superior comprehensive property. Graphical abstract: Highlights: Aligned pretreated nanofibers were used as precursor fibers for carbon nanofibers. Tension was exerted on the fiber during the carbonization process. Morphology and structural performance of carbon nanofibers were studied upon carbonization temperature. Carbon nanofibers carbonized at 1000 °C have possessed a sufficient carbonization degree and structural integrity.